2013
DOI: 10.1021/es403531d
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Biocides Irgarol and Terbutryn in the Biological Wastewater Treatment

Abstract: The biocides irgarol and terbutryn enter the wastewater treatment plant (WWTP) via combined sewer systems after leaching from coatings and paints of materials. In this study, the biotransformation of irgarol and terbutryn was examined in aerobic batch experiments with activated sludge taken from the nitrification zone of a conventional WWTP, since currently there is no information about the fate of irgarol and terbutryn in biological wastewater treatment. Both, irgarol and terbutryn were transformed into one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…It was found that TB provided one oxidation peak at the very positive potential values (about ?1950 mV) and this reaction had also irreversible character. The oxidation of TB to the appropriate sulfoxide or sulfone was described in the literature [52].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that TB provided one oxidation peak at the very positive potential values (about ?1950 mV) and this reaction had also irreversible character. The oxidation of TB to the appropriate sulfoxide or sulfone was described in the literature [52].…”
Section: Resultsmentioning
confidence: 99%
“…TPs for cases where MS spectra are not definitive (Wendel et al, 2014;Luft et al, 2014). Further 321 chemical characterization of transformation products will be done using 2-dimensional NMR 322 spectroscopy on transformation products isolated with preparative-LC, and further mass 323 spectrometry analyses will be performed using targeted MS/MS on selected degradation products.…”
Section: Transformation Products 280mentioning
confidence: 99%
“…2 and Table 1. Phycocyanin in IOM and FA has been reported to act as a photo-sensitizer under sunlight irradiation and therefore may have facilitated the reactions by producing various ROSs, including 1 DO 2 , Å OH, and excited-state DOM, presumably 3 …”
Section: Direct and Indirect Photo-degradation Kinetics Of Diuronmentioning
confidence: 99%
“…Emerging contaminants, including pharmaceuticals and personal care products (PPCPs), endocrine-disrupting chemicals (EDCs) and biocides, have been frequently detected at alarming concentrations in rivers, lakes and reservoirs [1][2][3][4]. Worse still, many of these contaminants are recalcitrant to the conventional physicochemical processes in wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation